Monitoring Proyek Akhir Mahasiswa Berbasis Android Pada Sistem Informasi Manajemen PENS - Sekar Puranti, Zazabillah; Yuwono, Wiratmoko; Asmara, Rengga (Technomedia Journal, 2022)
ABSTRACT The final project monitoring activity takes place in the university area, where the final project is one of the requirements for students to receive graduation from the campus. At the Electronic Engineering Polytechnic Institute of Surabaya, there is already a website-based final project monitoring application. However, the application is still based on a website, access for supervisors requires a VPN, and there are no reminders for students, supervisors, and examiners which will have a fatal impact on students if the final project monitoring process is not carried out properly. Due to some of these problems, this final report research aims to create an android-based final project monitoring application. This application will assist users in monitoring the final project because access via mobile phones will be easier and no longer need to use a VPN. The application is also equipped with a reminder feature so that users do not forget during the process of monitoring the final project. Keywords Monitoring, Final Project, Android, Electronic Engineering Polytechnic Institute of Surabaya